The Use of Artificial Intelligence-Based Translation Tools for Language Department Students - Dafallah Ibrahim; Yousuf Aboujanah; Khuloud Alouzi; Hajer Albshkar; Mohieddin Masoud; Sumaia Almajri (Journal of Arabic Literature, Teaching and Learning, 2025)
This study explores the integration and use of Artificial Intelligence translation tools among university level language students engaged in Arabic-English and English-Arabic translation tasks. With the increasing availability and sophistication of AI-based translation tools such as Google Translate, DeepSeek, and ChatGPT, translation tasks are experiencing a revolutionary paradigm shift. Drawing on qualitative and quantitative data collected from undergraduate students at a Libyan university, this research investigates students' attitudes toward AI-based translation tools, their frequency and purpose of use, perceived benefits and limitations, and the implications for translation teaching and practices. The findings reveal a strong engagement with AI-based translation tools, primarily for vocabulary learning, initial text drafts, and understanding complex sentence structures. However, challenges such as overreliance, inaccurate cultural, literal, scientific or idiomatic rendering, and limited post-editing skills are also evident. The study highlights the urgent need for pedagogical strategies that integrate AI-based translation tools within a framework of critical literacy and human supervision and intervention.